Feed intake and kidding rate of goats under intensive and semi-intensive management systems in Peninsular Malaysia - Abdul Halim, Norhazirah; Shohaimi, Shamarina; Nulit, Rosimah; Shikh Maidin, Mashitah (Department of Biology, Faculty of Science, Universiti Putra Malaysia, 2014)
Reproductive efficiency of goat production in Malaysia is low, despite an increase in production of kidding rate from year to year. It has been reported that, feed intake most probably affect the reproductive performance of goat by redusing the kidding rate and this has commonly been shown in sheep. With this unease, therefore, we assess the effect of dietary intake and kidding rate of three common breeds in Peninsular Malaysia (Boer, Jamnapari and Katjang) in two different animal husbandries; semi-intensive and intensive management system. A survey on type of feed intakes and kidding rate of goats were conducted from intensive and semi-intensive management farms in every states of Peninsular Malaysia from January 2014 until July 2014. Results show that the breed of goats (Boer, Jamnapari and Katjang) and the feed intake (Napier grass, soya hulls, oil palm fronds and pellet) do not have any significant effect on the kidding rate of goats in Peninsular Malaysia under intensive and semi-intensive system (p>0.05). The mean kidding rate ± SD of goats for intensive management system was 1.22 ± 0.64 while for semi-intensive management system the kidding rate was 1.08 ± 0.53 (p>0.05). Although the feeding systems for intensive farms seems to be more controlled and generally well-managed compared to the semi-intensive system, the kidding rate between each breed at both farm management systems were not significantly (p>0.05). A further study should be done in details on amount and frequency of feeds given in a day.